Enhanced hydrogen production over incorporated Cu and Ni into titania photocatalyst in glycerol-based photoelectrochemical cell: Effect of total metal loading and calcination temperature - Bashiri, R. (Elsevier Ltd, 2017)
The solar driven hydrogen production was successfully investigated in a glycerol-based photoelectrochemical cell (PEC) over nanostructured TiO2 supported bimetallic Cu and Ni by adjusting total metal loading (5, 10, and 15 mol) and calcination temperature (400, 450, 500, and 600 °C). The effects of the mentioned parameters on physicochemical and photoelectrochemical properties of prepared Cu–Ni/TiO2 photoanodes were explored by using different characterization techniques. The hydrogen evolution was experimentally found to be affected total metal loading and calcination temperature. The calcined photocatalyst with the total metal loading of 5 mol at 450 °C was identified as the most efficient photocatalyst by producing maximum accumulative hydrogen of 694.84 μmol. A high performance of this photocatalyst is mainly attributed to its proper particle size and great ratio of Ti3+:Ti4+ and Cu+:Cu2+ in TiO2 matrix. These better physicochemical properties enhanced charge carrier separation, which retarded the charge recombination and enhanced the transportation of photo-induced electrons at the photoelectrode/electrolyte interface. The intermediates from photooxidation of glycerol were verified using high performance liquid chromatography, indicating a partial oxidation of glycerol with selective pathway in KOH (1 M) solution. This work demonstrates that optimization Cu–Ni/TiO2 photoanode has the practical potential in PEC cell to generate hydrogen from solar and biomass energy. © 2017